Artificial Intelligence in the Fourth Industrial Revolution to Educate for Sustainable Development - Ally, Mohamed; Perris, Kirk (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2022)
There has been increasing interest in the use of Fourth Industrial Revolution technologies such as artificial intelligence to help achieve the Sustainable Development Goals. Recently, multilateral organizations have sponsored initiatives to make countries aware of the benefits of using artificial intelligence for sustainable development and to educate citizens to improve quality of life. This paper explores aspects of employing artificial intelligence for sustainable development, with a focus on lifelong learning, and inclusive and equitable quality education. Data are drawn from a thematic review of 32 academic peer-reviewed journal articles and interviews with six international experts. Findings include examples of benefits and challenges of artificial intelligence to address sustainable development and education.